Acute Toxicity Test of Lancing Leaf Extract (Solanum Mauritianum Scop.) as Well as Determination of Ld50 Values and Histopathology in Male Mice (Wistar Rat) - Afifah Ikhwan; Erny Tandanu; Ali Napiah Nasution; Refi Ikhtiari (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study is to find out about the acute toxicity test and analysis of its activity on lancing leaves. This research method is an experimental method including sampling and sample processing, extract making, acute toxicity tests, research on toxic symptoms in animals, organ harvesting, organ weighing, organ histopathology examination and data analysis with Statistical Program Service Solution (SPSS).  The research was conducted at the Integrated Development and Research Laboratory of Andalas University from September 2024 to December 2024. The tools used in this study are Rotary evaporator (Buchi R-210 Rotavapor), separation funnel, oven (Memmert), furnace, analytical scale (SF-400), decigator, mortar and pestle, porcelain cruce, Moisture Analyzer, Hot plate, Uv-Visible lamp (Camag), dark bottle, funnel, infusion bottle (500 ml and 100 ml), glass beaker (Pyrex), drip plate, rack and test tube, measuring cup (Pyrex), measuring flask,  spatels, stirring rods, droppers, ointment pots, object glass, KLT chambers, capillary pipes, syringes, sondes, animal cages, animal feeding and drinking places. The animals that will be used in this study are healthy male white rats aged 2-3 months with a body weight of 200-300 g and have never been used for experiments as many as 25 animalsAn LD50 value was obtained with a mild toxic value (>2000 mg/KgBB – 5000 mg/KgBB) against the acute toxicity test of lancing leaf extract (Solanum Mauritianum Scop.) in male rats. There was no significant difference between groups (p>0.05) in the body and BOR of male rats compared to the control group after administration of lancing leaf extract (Solanum Mauritianum Scop.).